The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1101/2020.07.08.20141218
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diagnostic and prognostic value of hematological and immunological markers in COVID-19 infection: A meta-analysis of 6320 patients

Abstract: Objective Evidence-based characterization of the diagnostic and prognostic value of the hematological and immunological markers related to the epidemic of Coronavirus Disease 2019 (COVID-19) is critical to understand the clinical course of the infection and to assess in development and validation of biomarkers. Methods Based on systematic search in Web of Science, PubMed, Scopus, and Science Direct up to April 22, 2020, a total of 52 eligible articles with 6,320 laboratory-confirmed COVID-19 cohorts w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
39
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 80 publications
5
39
0
2
Order By: Relevance
“…( Harrison et al, 2020 ) On the other side, a meta-analysis study has shown that a high level of leukocyte counts and the high neutrophil-lymphocyte ratio was associated with a higher risk of developing severe COVID-19 and mortality from COVID-19. ( Elshazli et al, 2020 ) Finally, people with dementia, due to the nature of their cognitive decline, would require the care and support of carers such as dementia caregivers in order to be able to follow healthcare and preventive measures such as wearing face masks and washing their hands with water and soap or hand sanitizers. ( Suzuki et al, 2020 ) However, during this COVID-19 pandemic, the availability of caregivers becomes limited which may cause dementia patients unable to follow healthcare and preventive measures therefore making them posed a higher risk of contracting an infection from COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…( Harrison et al, 2020 ) On the other side, a meta-analysis study has shown that a high level of leukocyte counts and the high neutrophil-lymphocyte ratio was associated with a higher risk of developing severe COVID-19 and mortality from COVID-19. ( Elshazli et al, 2020 ) Finally, people with dementia, due to the nature of their cognitive decline, would require the care and support of carers such as dementia caregivers in order to be able to follow healthcare and preventive measures such as wearing face masks and washing their hands with water and soap or hand sanitizers. ( Suzuki et al, 2020 ) However, during this COVID-19 pandemic, the availability of caregivers becomes limited which may cause dementia patients unable to follow healthcare and preventive measures therefore making them posed a higher risk of contracting an infection from COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…However, performance of prognosis for progression to severe disease was poorer with AUC = 0.75. In the recently reported meta-analysis over a large number of studies, classifier performance was found to be higher for neutrophil count (AUC = 0.831), lymphocyte (AUC = 0.867) and D-dimer (AUC = 0.876) than using IL-6 as covariate(AUC = 0.632) [ 13 ]. Another research with 102 COVID-19 patients used logistic regression to evaluate potential of multiple cytokines to diagnose severe and critical patients [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recently published extensive meta-analysis summarized elevated levels of IL-2, IL-2R, IL-4, IL-6, IL-8, IL-10, TNF-α and Interferon-γ (IFN-γ) in severe group of patients, whereas no significant increase was found in the levels of IL-1β and IL-17 [ 12 ]. A two-arm meta-analysis study synthesized from individual patient data reported statistically significant odds ratio (p < 0.05) to severe disease for only two cytokines - IL-6 and IL-10 [ 13 ]. Some meta-analysis efforts reported difference in IL-6 level between severe and non-severe COVID-19 patients in terms of Standardized Mean Difference (SMD) [ 14 ], mean difference [ 15 ] or ratio of means [ 16 ] values that can potentially be used as cut-off to discriminate between severe and non-severe patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings concur with those from other studies, suggesting admission CRP can guide the management of COVID-19. 6 …”
mentioning
confidence: 99%